2017
DOI: 10.1038/s41598-017-05951-4
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Tissue Inhibitor of Metalloproteinase-4 (TIMP4) ameliorates high fat diet-induced obesity in mice due to defective lipid absorption

Abstract: Tissue inhibitor of metalloproteases (TIMPs) are inhibitors of matrix metalloproteinases (MMPs) that regulate tissue extracellular matrix (ECM) turnover. TIMP4 is highly expressed in adipose tissue, its levels are further elevated following high-fat diet, but its role in obesity is unknown. Eight-week old wild-type (WT) and Timp4-knockout (Timp4 −/−) mice received chow or high fat diet (HFD) for twelve weeks. Timp4 −/− mice exhibited a higher food intake but lower body fat gain. Adipose tissue of Timp4 −/–-HFD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 42 publications
4
31
0
Order By: Relevance
“…Specifically, a TIMP-3 deletion in mice has pointed to cause hepatic steatosis and WAT inflammation [78] while an overexpression seemed to protect from them [79]. Relating to TIMP-4, recent studies have evidenced the pathogenic effect of TIMP-4 deregulation in IR in different rodent models [80,81].…”
Section: Structure Of Extracellular Matrix In the Adipose Tissue Amentioning
confidence: 99%
“…Specifically, a TIMP-3 deletion in mice has pointed to cause hepatic steatosis and WAT inflammation [78] while an overexpression seemed to protect from them [79]. Relating to TIMP-4, recent studies have evidenced the pathogenic effect of TIMP-4 deregulation in IR in different rodent models [80,81].…”
Section: Structure Of Extracellular Matrix In the Adipose Tissue Amentioning
confidence: 99%
“…There are some reports that heterozygous PPARγ-deficient mice are protected from HFD, aging-induced adipocyte hypertrophy, obesity, and insulin resistance [ 42 , 43 ]. Deletion of TIMP4 improves the obesity in HFD-induced experimental mice through impairment of lipid absorption [ 44 ]. Interestingly, our present study showed that the hepatic protein expression of PPARγ, ADRP, and TIMP4, were markedly elevated in the NASH mice group, but significantly reduced in the livers of LC treated mice ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…(2017) reported the association of TIMP4 rs3755724 with predictors of ≥5% weight loss. Furthermore, in a study of obesity, TIMP4 was associated with high fat diet-induced obesity and may act through the regulation of lipid absorption (Sakamuri et al., 2017). There is a growing awareness that steroid hormones may cause ONFH through disruptions to lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%